Heel lance in newborn during breastfeeding: an evaluation of analgesic effect of this procedure - Tozzini Danila; Rossi Maura; Ziliotto Anna; Trada Michela; Angilella Giuseppina; Alloni Viviana; Perino Antonella; Candriella Manuela; Uga Elena; Tripaldi Clelia; Vaglio Michela; Grossi Luigina; et al. (BMC, 2008)
Abstract Objectives The reduction of pain due to routine invasive procedures (capillary heel stick blood sampling for neonatal metabolic screening) in the newborn is an important objective for the so-called "Hospital with no pain". Practices such as skin to skin contact, or breastfeeding, in healthy newborn, may represent an alternative to the use of analgesic drugs. The aim of our work is to evaluate the analgesic effect of breastfeeding during heel puncture in full term healthy newborn. Methods We studied 200 healthy full term newborns (100 cases and 100 controls), proposing the puncture to mothers during breastfeeding, and explaining to them all the advantages of this practice. Pain assessment was evaluated by DAN scale (Douleur Aigue Nouveau ne scale). Results The difference in score of pain according to the DAN scale was significant in the two groups of patients (p = 0.000); the medium score was 5.15 for controls and 2.65 for cases (newborns sampled during breastfeeding). Conclusion Our results confirmed the evidence of analgesic effect of breastfeeding during heel puncture. This procedure could easily be adopted routinely in maternity wards.